REVITALISASI ASAS ETIS PEMERINTAHAN SEBAGAI UPAYA PEMBERANTASAN KEJAHATAN DAN KEKERASAN STRUKTURAL - ., Fadhilah (KYBERNAN: Jurnal Ilmiah Ilmu Pemerintahan, 2010)
This article is a study of literature, entitled ethical management principles for combating crime and structural violence revitalization efforts. Material object of this research is ethical principles and formal object is the Ethical Governance. The scope of discussion in this study is the importance of the relevance of ethical principles in the organization to the government's efforts to combat crime and violence that occurred in Indonesia in recent strultural. The purpose of this research is to restore the importance of moral values contained in the Code of Ethical Principles as social control to the b The method used in this study is a description and analysis of philosophical reflection.ureaucrats in the fight against crime and structural violence. The goal of this research is to see how far the relevance of moral values which become the handle of the bureaucrats in government relations for the fight against crime and structural violence. Results of this study is that the principle of ethical management remains an important role in managing the behaviour of officials to prevent violations of the public relations efforts to eliminate crime and structural violence.